Effectiveness of flipped classrooms in Chinese students of clinical medicine major undergoing clinical practice: a meta-analysis - Xinrui Sun; Xin Yuan; Linyu Zhang; Yi Zhang; Xue Xiao; Hanmin Liu; Fang Ma (BMC Medical Education)
Abstract Introduction Clinical practice is a cornerstone of undergraduate training in Chinese medical education, ensuring the development of essential skills for future professionals. While flipped classrooms have gained popularity for their potential to enhance learning outcomes, the effectiveness of this approach in clinical settings remains underexplored. This study aims to address this research gap by consolidating evidence on the impact of flipped classrooms through a comprehensive meta-analysis. Methods Two researchers independently screened all the retrieved articles and did data extraction. The Cochrane Risk of Bias tool for randomized trials was used for methodological quality assessment. Weighted mean differences (WMD) and 95% confidence interval (CI) were used to compare the differences in theoretical and skill scores between the flipped classrooms and traditional lecture groups. The Cochran Q test and the I2 statistic were used for heterogeneity analysis. The funnel plots were used to assess the publication bias. All analyses will be performed via RevMan version 5.3. Results A total of 19 studies were included in the final analysis, 18 of which were eligible for quantitative analysis. As a high level of heterogeneity of included studies, random effect models were used. Both the theoretical and skill scores in flipped classroom students were higher than those in traditional lecture students (SMD = 8.33, 95% CI: 5.91–10.75, P < 0.001; SMD = 7.91, 95% CI: 5.86–9.91, P < 0.001, respectively). However, all included studies were of poor quality, and funnel plots indicated the presence of publication bias. Conclusion Flipped classrooms demonstrate potential in improving both theoretical knowledge and practical skills among medical students in clinical practice. Despite these promising results, the interpretation is limited by methodological shortcomings and potential publication bias in the included studies. Future research should focus on conducting high-quality, large-scale trials to validate these findings and explore their broader applicability.